1997
DOI: 10.1063/1.364396
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of amorphous SiCxNy chemical vapor deposited coatings

Abstract: High Seebeck effects from conducting polymer: Poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) based thin-film device with hybrid metal/polymer/metal architecture APL: Org. Electron. Photonics 5, 238 (2012) High Seebeck effects from conducting polymer: Poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) based thin-film device with hybrid metal/polymer/metal architecture Appl. Phys. Lett. 101, 173304 (2012) Response to "Comment on 'Silver/silicon dioxide/silver sandwich films in the blue-to-red sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(43 citation statements)
references
References 64 publications
1
42
0
Order By: Relevance
“…The presence of hydrogen in our films is consistent with the literature data on the a-Si:C:N:H films deposited, at much higher substrate temperatures than in the present study, from organosilicon precursors by DP-CVD from hexamethyldsilazane at T S = 650 C, [41] and thermal CVD from ethylsilazane at T S = 800 C. [19] Although the absorption bands from hydrogen-containing groups were almost undetectable in the IR spectra of the films produced by both CVD techniques, the concentrations of hydrogen were about 40 at.-%, [41] and about 10 at.-%. [19] Moreover, the results of the study of DP-CVD from the SiH 4 /CH 4 /N 2 (or NH 3 ) mixture, [42] and thermal CVD from the Me 4 Si/NH 3 /H 2 mixture, [43] revealed that fully dehydrogenated SiCN films were formed at very high substrate temperatures, T S > 1000 C.…”
Section: Ftir Spectroscopymentioning
confidence: 96%
“…The presence of hydrogen in our films is consistent with the literature data on the a-Si:C:N:H films deposited, at much higher substrate temperatures than in the present study, from organosilicon precursors by DP-CVD from hexamethyldsilazane at T S = 650 C, [41] and thermal CVD from ethylsilazane at T S = 800 C. [19] Although the absorption bands from hydrogen-containing groups were almost undetectable in the IR spectra of the films produced by both CVD techniques, the concentrations of hydrogen were about 40 at.-%, [41] and about 10 at.-%. [19] Moreover, the results of the study of DP-CVD from the SiH 4 /CH 4 /N 2 (or NH 3 ) mixture, [42] and thermal CVD from the Me 4 Si/NH 3 /H 2 mixture, [43] revealed that fully dehydrogenated SiCN films were formed at very high substrate temperatures, T S > 1000 C.…”
Section: Ftir Spectroscopymentioning
confidence: 96%
“…So far, silicon carbonitride thin films have been effectively produced from organosilicon compounds as a single-source precursor by various chemical vapour deposition (CVD) techniques, including laser-induced CVD and PACVD with hexamethyldisilazane (HMDSN) [4][5][6][7] and bis(-trimethylsilyl)-carbodiimide (BTSC) [8][9] as the starting material. Thermally activated chemical vapour deposition at 1000-1200 C using tetramethylsilane (TMS), NH 3 and H 2 as the starting materials was also used to produce SiCN coatings [10] . A low substrate temperature is desirable for practical applications in electronic devices and protective coatings.…”
Section: Introductionmentioning
confidence: 99%
“…The SiC x N y coatings were obtained by CVD at 1000-1200 °C using TMS-NH 3 -H 2 (Bendeddouche et al, 1997). It was found that SiC x N y films are not simply a mixture of the phases SiC and Si 3 N 4 , and have a more complex relationship between the three elements, corresponding to the existence of Si(C 4-n N n ) units.…”
Section: Thermal Cvdmentioning
confidence: 99%
“…The heating up to 1650°C results in formation of a mixture of nanocomposites Si 3 N 4 /SiC or Si 3 N 4 /SiC/C. SiC x N y coatings were obtained by CVD at 1000-1200°C using TMS-NH 3 -H 2 (Bendeddouche et al, 1997). These coatings were analyzed by XPS, Raman spectrometry, FTIR, TEM/EELS and 29 Si magic-angle spinning NMR ( 29 Si MAS-NMR).…”
Section: Silicon Carbonitride Compoundsmentioning
confidence: 99%